Exploring the Relationship between Formal Management Control Systems, Organisational Performance and Innovation: The Role of Leadership Characteristics - Dhiona Ayu Nani; Vera Apri Dina Safitri (Asian Journal of Business and Accounting, 2021)
ABSTRACT Manuscript type: Research paper Research aims: This study aims to examine the relationship between the formal management control system (MCS) on organisational performance and innovation. It also evaluates the role of leadership characteristics as the moderating variable between MCS and innovation. Design/Methodology/Approach: This study employs a survey questionnaire, and data collected from business units of Indonesian manufacturing and services firms. The warp partial least squares structural equation modeling (PLS-SEM) approach was employed to analyse the data and test the proposed model. Research findings: The findings demonstrate that: (1) A welldesigned formal MCS can improve organisational performance and innovation; (2) managers with good characteristics such as showing good behaviour through compliance with company rules, involving themselves in subordinates’ activities, and supporting subordinates’ ideas, can improve subordinates’ creativity in producing innovation. Theoretical contribution/Originality: This study expands the existing literature by examining the role of leadership characteristics as a moderating variable between the formal management control system (MCS) and innovation. Practitioner/Policy implications: The findings of this study demonstrate that, for Indonesian firms to compete in globally-competitive markets, they need to implement well-designed formal MCS. For formal MCS to contribute to innovation, managers who demonstrate good leadership characteristics are crucial. Research limitation/Implications: Future research can investigate comparative analyses of different ASEAN countries since different Asian countries have different dominant cultures and values, which may have some impact on MCS, organisational performance and innovation. It may also consider how different types of MCS improve organisational performance and innovation performance. Keywords: Management Control Systems, Organisational Performance, Innovation, Leadership Characteristics JEL Classification: M41